Hesperidin Increases Cytotoxic Activity of Doxorubicin on Hela Cell Line Through Cell Cycle Modulation and Apoptotis Induction - Kusharyanti, Indri; Larasati, .; Susidarti, Ratna Asmah; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2011)
Combination of chemotherapeutic agent and chemo preventiveagent is being a new approach in cancer treatment.This is aimed at enhancing the effectivity and also reducing drugresistance and adverse side effect of the chemo therapeuticagent.Hesperidin,acitrus flavonoid has reported to reduce theproliferation of many cancer cells.The objectives of this study were to investigate cytotoxic activities, cell cycle modulation and apoptosis induction of he speridinand its combination withdoxorubicinon Helacelllines.MTT [3-(4,5-dimethylthiazol-2-yl)-2.5-diphenyltetrazoliumbromide] assay was used tomeasure the growth inhibitory effect of he speridinanditscombination with doxorubicinon Helacells.Cellcycle profile was determined by flowcytometry and the dataobtained was analyzed by using Mod Fit LT3.0program.Apoptos is assay was done using double staining method usingethidium$bromideandacridine$orange.Hesperidin inhibited cellgrowth with IC5048M, while the IC50 of doxorubicin was 1000nM.Combination of 500n Mdoxorubicin and 6M hesperidin showed strongest inhibitory effect toward Hela cells. Hesperidin of 24 2M accumulated HeLacells at G1phase,butit scombinationwith 500nM Doxorubicin gave G1 and Sphase accumulation at 24h incubation.Both of Hesperidin and Doxorubicin were capable of inducing apoptosis.Inaccordance of the apoptoticeffect,hesperidin,doxorubicin and their combination decreasedthe expression Bcl$2 and increased the expression of Bax. Accordingtothisresult,hesperidinhasapotencytobedevelopedasco$chemotherapeutic agent forcervical cancer. KeyÃÂ ÃÂ  ÃÂ words:Cochemotherapy,Hesperidin,Doxorubicin,Hela,MTTassay